Abrogation of USP7 is an alternative strategy to downregulate PD-L1 and sensitize gastric cancer cells to T cells killing - Zhiru Wang; Wenting Kang; Ouwen Li; Fengyu Qi; Junwei Wang; Yinghua You; Pengxing He; Zhenhe Suo; Yichao Zheng; Hong-Min Liu (Elsevier, 2021)
Targeting immune checkpoints such as programmed cell death protein 1 (PD-1) and programmed death ligand-1 (PD-L1) have been approved for treating melanoma, gastric cancer (GC) and bladder cancer with clinical benefit. Nevertheless, many patients failed to respond to anti-PD-1/PD-L1 treatment, so it is necessary to seek an alternative strategy for traditional PD-1/PD-L1 targeting immunotherapy. Here with the data from The Cancer Genome Atlas (TCGA) and our in-house tissue library, PD-L1 expression was found to be positively correlated with the expression of ubiquitin-specific processing protease 7 (USP7) in GC. Furthermore, USP7 directly interacted with PD-L1 in order to stabilize it, while abrogation of USP7 attenuated PD-L1/PD-1 interaction and sensitized cancer cells to T cell killing in vitro and in vivo. Besides, USP7 inhibitor suppressed GC cells proliferation by stabilizing P53 in vitro and in vivo. Collectively, our findings indicate that in addition to inhibiting cancer cells proliferation, USP7 inhibitor can also downregulate PD-L1 expression to enhance anti-tumor immune response simultaneously. Hence, these data posit USP7 inhibitor as an anti-proliferation agent as well as a novel therapeutic agent in PD-L1/PD-1 blockade strategy that can promote the immune response of the tumor.